RISK MANAGEMENT IN THE FINANCIAL SECTOR OF UKRAINE IN THE CONTEXT OF CYBER THREATS AND POST-PANDEMIC ECONOMIC RECOVERY (INNOVATIVE ECONOMY, 2021)
Demchyshak N.B., Shkyria A.S. RISK MANAGEMENT IN THE FINANCIAL SECTOR OF UKRAINE IN THE CONTEXT OF CYBER THREATS AND POST-PANDEMIC ECONOMIC RECOVERYPurpose. The aim of the article is substantiation of approaches of domestic and foreign scientists to risk management in the financial sector of Ukraine in the context of cyber threats and the need to ensure national security and post-pandemic economic recovery.Methodology of research. General scientific and special methods of scientific research are used in the article, in particular: induction, deduction, scientific abstraction - to reveal the essence of the concepts of "cyber threat", “cyber security" and "digitalization"; statistical and graphical methods - to assess the current situation in the field of cyber defence in the world and the national cyber security index; methods of analysis and synthesis - in substantiating the conclusions of the research.Finding. Definitions of cyber risk, approaches to its interpretation and classification were considered. The importance of cyber security in the digitalization of the national economy was argued. The Strategy of Ukrainian Financial Sector Development until 2025 is analysed. The world statistics of frequency and losses due to cyber-attacks are studied and the cyber threats that caused the greatest losses in Ukraine are identified. The analysis of Ukraine’s positions in the National Cyber Security Index 2020 is carried out. The directions of cyber threat prevention that can be useful for Ukrainian companies are substantiated.Originality. The author’s definition of the term "cyber risk" is proposed, in which special attention in focused on the effects of cyber threats. The importance of cyber risk management in the conditions of inevitability of digitalization in the financial sector of Ukraine is substantiated. Approaches to the prevention of cyber-attacks, the implementation of which is necessary for the successful digital transformation of Ukraine, are proposed.Practical value. The results of the research will contribute to the formation of an effective risk management system in the financial sector of Ukraine in terms of digitalization of the financial space and post-pandemic recovery of the national economy.Key words: national security, cyber risk, cyber threat, cyber defence, digitalization, post-pandemic recovery, fintech.
Keywords: Key words; national security; cyber risk; cyber threat; cyber defence; digitalization; post-pandemic recovery; fintech.